Enhanced immune response to MMP3 stimulation in microglia expressing mutant huntingtin. (14th June 2016) - Connolly, C.; Magnusson-Lind, A.; Lu, G.; Wagner, P.K.; Southwell, A.L.; Hayden, M.R.; Björkqvist, M.; Leavitt, B.R.
Highlights: Increased secretion of cytokines from microglia containing mutant huntingtin. Decreasing mutant huntingtin can ameliorate the mutant huntingtin over secretion phenotype. MMP3 an endogenous brain signal can activate microglia similar to pro-inflammatory stimuli, LPS. MMPs correlate with worsening of HD. Abstract: Huntington's Disease (HD) is an inherited neurodegenerative disease caused by a polyglutamine expansion in the huntingtin protein. The YAC128 mouse model of HD expresses the full-length human huntingtin protein with 128 CAG repeats and replicates the phenotype and neurodegeneration that occur in HD. Several studies have implicated a role for neuroinflammation in HD pathogenesis. Studies on presymptomatic HD patients have illustrated microgliosis (activated microglia) in brain regions affected in HD. Mutant huntingtin expressing isolated primary monocytes (human HD patients) and primary macrophages (YAC128) are overactive in response to lipopolysaccharide (LPS) stimulation. In this study we demonstrate that cultured primary microglia (the resident immune cells of the brain cells) from YAC128 mice differentially express a wide number of cytokines compared to wildtype microglia cultures in response to LPS. Furthermore, this study outlines a direct interaction between mutant huntingtin and cytokine secretion in HD microglia. Increased cytokine release in YAC128 microglia can be blocked by cannabinoid activation or by mutant huntingtin knockdown with anti-sense oligonucleotide treatment. Matrix metalloprotease 3 (MMP3), an endogenous neuronal activator of microglia, also induces increased cytokine release from YAC128 microglia compared to wildtype microglia. We found elevated MMP levels in HD CSF, and MMP levels correlate with disease severity in HD. These data support a novel role for MMPs and microglial activation in HD pathogenesis. With an improved understanding of the specific cellular processes involved in HD neuroinflammation, novel therapeutic agents targeting these processes can be developed and hold great promise in the treatment of HD.